Pendampingan hafalan Al Qur’an juz 30 dengan menggunakan metode pendengaran (murottal) pada peserta didik di sekolah dasar - Insiyah, Muzdalifatul; Nurussa’adah, Awwaliya; Fajrani, Wahyu Afrina; Maghfiroh, Fadhilah Syarafina; Lina, Marisa Fran (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
This study examines the implementation of a listening-based method (murottal) to strengthen elementary students' memorization of Juz 30. The topic is important because the choice of memorization approach can affect recitation accuracy and fluency, as well as students' consistency in Qur'anic memorization. The study aims to understand better how students memorize Juz 30 using the murottal method. Using a qualitative field research design conducted at SDN Salatiga 3, the study involved all Muslim students in grades 1 through 6, with the listening (murottal) method as the primary focus of analysis. The findings indicate that applying the murottal listening method at SDN Salatiga 3 had a positive impact on students' memorization outcomes for Juz 30.